2022
DOI: 10.1001/jamanetworkopen.2021.41772
|View full text |Cite
|
Sign up to set email alerts
|

Association of Depression With Atrial Fibrillation in South Korean Adults

Abstract: IMPORTANCEThe risk of atrial fibrillation (AF) in people with depression is not fully known.Depression is associated with sympathetic activation and emotional stress, which might increase the risk of new-onset AF.OBJECTIVE To assess the incidence of new-onset AF in those with and without depression using data from a nationwide health care database. DESIGN, SETTING, AND PARTICIPANTSThis cohort study obtained data from the Korean National Health Insurance Service database and enrolled people who underwent a nati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…However, the substantial heterogeneity of our investigation still exists. After removing the study from Kim et al ( 37 ), the outcome was not influenced and the heterogeneity is acceptable. The sources of heterogeneity are speculated as follows: (1) The race difference between this study and other included studies was non-negligible.…”
Section: Discussionmentioning
confidence: 99%
“…However, the substantial heterogeneity of our investigation still exists. After removing the study from Kim et al ( 37 ), the outcome was not influenced and the heterogeneity is acceptable. The sources of heterogeneity are speculated as follows: (1) The race difference between this study and other included studies was non-negligible.…”
Section: Discussionmentioning
confidence: 99%
“…Whether psychological factors increase the risk of AF has been controversial among previous studies. 26 , 27 , 28 , 29 In the recent meta-analyses, the risk of AF was increased by anxiety, anger, depression, antidepressant use, and work stress. 30 , 31 These studies focused on the psychological traits that seem to be the result of neuroticism coping with the outer stimulus and not neuroticism itself.…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between depression and AF onset, severity, and complications has been previously studied and has revealed variable results. A large South Korean cohort study with more than ve million participants found that there is a link between depression and a higher risk of developing new-onset AF, and those who have recurring periods of depression are at greater risk [23]. Similar results were reported in a previous large meta-analysis that found that negative psychological characteristics such as anxiety, anger, depression, and work stress were associated with an increased risk of atrial brillation (AF), with anxiety and depression linked to 10% and 25% increases in the incidence of AF, respectively.…”
Section: Discussionmentioning
confidence: 99%